The historical Domitian - illustrating some problems of historiography - Botha, P. J. J. (Neotestamentica, 1989)
The ""quest for the historical Domitian"" provides a good example of the problems a historian has to grapple with, especially when the sources are very limited and biased and a strong tradition to pre-judge the issues exist. This paper discusses some relevant theoretical aspects of historical research, the major sources for knowledge of Domitian, and develops a context within which one can understand the opposition and persecution encountered under Domitian. It adds up to a preliminary study: prolegomena to a more complete historical reconstruction - illustrating the need of such an attempt as part of all historiography.